Moral e educação em Kant: Contribuições para a formação de indivíduos autônomos - Grangeiro, Brendha Maria Malheiro (2019)
The present work deals with the problematic of the moral and education in Kant, as well as the contributions for the formation of autonomous individuals. In this perspective, initially we will focus on moral questions, seeking to understand, through this thought analysis, the ideas that constitute his moral theory and how this conception is articulated. So, this paper seeks to reflect, in the light of Kant’s thought, the relation between the concepts of will, duty, freedom and autonomy. Consequently, we strive to present and analyze the concept of virtue and all that it can represent in relation to the moral improvement of individuals. For this reason, we expose the duties that encompass the ends of one’s own perfection and the happiness of others that understand the moral force capable of achieving in the individual the overcoming of his state of heteronomy through the formation of his own character. Thus, the educational proposal arises and has as a pretension, through the concepts of physical and practical education, to assist in the formation of autonomous individuals capable of discerning and making use of the moral concepts acquired throughout the process to obtain morality. The man is the only creature who needs to be educated and it will be, because it’s through moral education that it will become viable the exit from animality, a state of heteronomy, to humanity and autonomy, where discipline and education are fundamental to the exercise of reason.